Management of mild traumatic brain injury. Issue 3 (9th April 2020) - van Gils, Anne; Stone, Jon; Welch, Killian; Davidson, Louise R; Kerslake, Dean; Caesar, Dave; McWhirter, Laura; Carson, Alan
Abstract : Mild traumatic brain injury (TBI) is common and associated with a range of diffuse, non-specific symptoms including headache, nausea, dizziness, fatigue, hypersomnolence, attentional difficulties, photosensitivity and phonosensitivity, irritability and depersonalisation. Although these symptoms usually resolve within 3 months, 5%–15% of patients are left with chronic symptoms. We argue that simply labelling such symptoms as 'postconcussional' is of little benefit to patients. Instead, we suggest that detailed assessment, including investigation, both of the severity of the 'mild' injury and of the individual symptom syndromes, should be used to tailor a rehabilitative approach to symptoms. To complement such an approach, we have developed a self-help website for patients with mild TBI, based on neurorehabilitative and cognitive behavioural therapy principles, offering information, tips and tools to guide recovery: www.headinjurysymptoms.org .